2022
DOI: 10.3390/ijms23042117
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Mediates EMT Gene Expression in Human Pancreatic Ductal Adenocarcinoma Cell Lines

Abstract: Due to abundant stroma and extracellular matrix, accompanied by lack of vascularization, pancreatic ductal adenocarcinoma (PDAC) is characterized by severe hypoxia. Epigenetic regulation is likely one of the mechanisms driving hypoxia-induced epithelial-to-mesenchymal transition (EMT), responsible for PDAC aggressiveness and dismal prognosis. To verify the role of DNA methylation in this process, we assessed gene expression and DNA methylation changes in four PDAC cell lines. BxPC-3, MIA PaCa-2, PANC-1, and SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Similarly, the mRNA expression of CMYC, a marker of cell proliferation, was statistically reduced at 25 nM EC359 ( Figure 3 B). EC359 also reduced the expression of the EMT’s biomarkers Vimentin and Snail Family Transcriptional Repressor 1 (SNAIL-1) along with the expression of Chemokine receptor type 4 (CXCR4), a biomarker of PDAC aggressiveness that was also upregulated in the PADC tissues ( Figure 3 B) [ 43 ]. Vimentin is required for cell transition from the EMT state [ 44 ], and as shown in Figure 3 B, LIFR inhibition decreased both the genes as well as the assembly of vimentin filaments [ Figure 3 B] that are essential for cytoskeleton reorganization, cell spreading, and migration.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the mRNA expression of CMYC, a marker of cell proliferation, was statistically reduced at 25 nM EC359 ( Figure 3 B). EC359 also reduced the expression of the EMT’s biomarkers Vimentin and Snail Family Transcriptional Repressor 1 (SNAIL-1) along with the expression of Chemokine receptor type 4 (CXCR4), a biomarker of PDAC aggressiveness that was also upregulated in the PADC tissues ( Figure 3 B) [ 43 ]. Vimentin is required for cell transition from the EMT state [ 44 ], and as shown in Figure 3 B, LIFR inhibition decreased both the genes as well as the assembly of vimentin filaments [ Figure 3 B] that are essential for cytoskeleton reorganization, cell spreading, and migration.…”
Section: Resultsmentioning
confidence: 99%
“…There have been several studies considering the effects of PDAC-cell-derived CM on other stromal components such as fibroblasts [ 11 ] and vice versa [ 20 , 21 ]. This work, however, is one of the first to consider the effects of PDAC-cell-derived CM on PC cells directly and specifically during gemcitabine and TRAIL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Their availability increase research efforts in the field of cancer research. As such, these cell lines have been used to study different aspects of pancreatic cancer, including DNA methylation, RNA splicing, histone modification, EMT, TGFβ signaling, and anticancer drug testing 154–157 . Results from these studies have shown correlations between gene expression, activation of specific cellular pathways, and drug response.…”
Section: Late Diagnosismentioning
confidence: 99%